Building scalable apps with Redis and Node.js : develop customized, scalable web apps through the integration of powerful Node.js frameworks - Johanan, Joshua (Community experience distilled., 2014)
If the phrase scalability sounds alien to you, then this is an ideal book for you. You will not need much Node.js experience as each framework is demonstrated in a way that requires no previous knowledge of the framework. You will be building scalable Node.js applications in no time! Knowledge of JavaScript is required.